1985
DOI: 10.1093/ptj/65.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Isometric Strength of the Quadriceps Femoris Muscle After Training with Electrical Stimulation

Abstract: The purpose of this investigation was to determine if training isometrically with electrical stimulation (ES) alone would significantly increase isometric strength of the quadriceps femoris muscle. The relationships between the strength changes and the relative force and duration of training contractions were also studied. An experimental group (Group 1) and a control group (Group 2), 12 subjects in each, underwent pretesting and posttesting to obtain their maximum voluntary isometric contractions (MVICs). Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
117
0
14

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(138 citation statements)
references
References 21 publications
7
117
0
14
Order By: Relevance
“…As already pointed out in a recent review published in this journal (Maffiuletti 2010), the so-called training intensity (i.e., the level of force evoked by NMES, expressed as a fraction of the MVC force) seems to be the main determinant of NMES training effectiveness. In other words, muscles should produce the greatest relative tension when stimulated by NMES in order to maximize the training-induced strength gains (Lai et al 1988;Selkowitz 1985). Interestingly, we plotted the MVC strength gains collected from different NMES training studies completed in our laboratory against respective training intensities, and confirmed that a doseresponse relation does exist between these two variables (Maffiuletti NA, unpublished observations).…”
Section: Nmes Applicationssupporting
confidence: 57%
“…As already pointed out in a recent review published in this journal (Maffiuletti 2010), the so-called training intensity (i.e., the level of force evoked by NMES, expressed as a fraction of the MVC force) seems to be the main determinant of NMES training effectiveness. In other words, muscles should produce the greatest relative tension when stimulated by NMES in order to maximize the training-induced strength gains (Lai et al 1988;Selkowitz 1985). Interestingly, we plotted the MVC strength gains collected from different NMES training studies completed in our laboratory against respective training intensities, and confirmed that a doseresponse relation does exist between these two variables (Maffiuletti NA, unpublished observations).…”
Section: Nmes Applicationssupporting
confidence: 57%
“…We did not measure torque production during treatment in our study, however, it has been demonstrated that increased contraction inten-sity produced during NMES treatment results in proportionally increased improvements in isometric strength. 3,17,20 Differences in contraction intensity between the 2 types of NMES applications could explain the differences in treatment effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Its therapeutic use seeks primarily to accelerate the healing processes, gain muscle strength, improve general physical condition, and improve quality of life. It shows positive results regarding regaining strength, endurance, and muscle hypertrophy.…”
Section: Neuromuscular Electrostimulation (Nmes)mentioning
confidence: 99%